If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2t + -2 = 3t + 2 Reorder the terms: -2 + 2t = 3t + 2 Reorder the terms: -2 + 2t = 2 + 3t Solving -2 + 2t = 2 + 3t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-3t' to each side of the equation. -2 + 2t + -3t = 2 + 3t + -3t Combine like terms: 2t + -3t = -1t -2 + -1t = 2 + 3t + -3t Combine like terms: 3t + -3t = 0 -2 + -1t = 2 + 0 -2 + -1t = 2 Add '2' to each side of the equation. -2 + 2 + -1t = 2 + 2 Combine like terms: -2 + 2 = 0 0 + -1t = 2 + 2 -1t = 2 + 2 Combine like terms: 2 + 2 = 4 -1t = 4 Divide each side by '-1'. t = -4 Simplifying t = -4
| -3a(-10)=16 | | (x)(2x-3)=27 | | T-1/4=11/4 | | 2x+-6=8 | | h(t)=-16t^2+79t+5 | | y=(2x-1)(3x+2) | | 4t=16.11-0.0062y | | -x(7)=-40 | | y=(2x-1)(3x-1) | | 4-√-12/4 | | t=16.11-0.0062 | | -7t^2+7t+8t^3-t^3+15t^2-4t= | | 5+8(X-2)=11-7(X-8) | | x(x-6)-x^2-5x-7=0 | | p(x)=(500-x)/20 | | X/100=27/64 | | x(x-6)=x^2+5x+7 | | -4(x-9)=-9x+6 | | -7(t-8)-(t+3)=10 | | X+6y+4z=-13 | | (4x+2)(2x+1)=0 | | x=5000/40/x-10/x | | 4x-9=-18 | | .15x=3800 | | -3x-Y-z=-6 | | 7x+54=9(x+6)-2x | | t-1/4=7/4 | | 5+8(x-2)=7(x-8) | | x*12=44800 | | x*44800= | | -4+4x=4(x-1) | | 8y=16+-2x |